Complementing outcome-based education: the implementation of student learning time - Alias, Asmidar; Mohamad Bhkari, Norshariza; Mohsan, Nor Maslina; Ariffin, Kamisah (Universiti Teknologi MARA, 2009)
One of the important elements in the Outcome-Based Education (OBE) is Student Learning Time (SLT). SLT serves as a guideline for instructors in planning their work and designing assessments for a respective subject within the given credit hours. SLT can also avoid the tendency to overload students with assignments without considering their effective learning hours, obligation to other subjects and time needed to develop skills out of classroom contact. This paper describes the notion of SLT according to the projection cumulative hours of face-to-face and non face-to-face components. Specifically, it shares the UiTM Pahang Faculty of Engineering's approach to implementing SLT in complementing the OBE requirements. This practice sharing information can be a useful guide for instructors to allocate and organise their teaching hours more effectively, and in turn, comply with the OBE practices and requirements.